THE SYSTEMATIC REVIEW OF ADIPOCYTES IN ACUTE LEUKEMIA - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Adipose tissue, a major cell type in the bone marrow microenvironment, plays a crucial role in the development and progression of cancer. Adipocytes, which make up the majority of cells in adipose tissue, exhibit distinct metabolic roles, replication and development abilities, cytokine production, and reactions to external stimuli. Adipocytes are abundant in bone marrow, a key site of metastasis for solid tumors and a crucial microenvironment for hematological malignancies. The aim: This study aims to determine the association of adipocytes in acute leukemia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like PubMed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 27 articles, whereas the results of our search on ScienceDirect brought up 281 articles. The results of the search conducted by title screening yielded a total 14 articles for PubMed and 3 articles for ScienceDirect. We compiled a total of 12 papers, 10 of which came from PubMed and 2 of which came from ScienceDirect. We excluded 4 review articles, 2 articles having ineligible subjects, and 1 article having insufficient outcomes. In the end, we included five research that met the criteria. Conclusion: Acute leukemia cells have various effects on adipocytes which alter adipogenic differentiation capacities or adipocyte lipolysis and promote bone marrow adipocyte remodeling. Adipocytes play a crucial role in acute leukemia cell survival and their treatment.